Ureteric nephrogenic adenoma: A report of two cases - Mudassar Hussain; Nasir U Din; Haseeb A Khan; Muhammad Tehseen (Wolters Kluwer Medknow Publications, 2012)
Nephrogenic adenoma is a rare, benign, metaplastic lesion predominantly seen in urinary bladder, which occurs even more rarely in the ureters. We report two such cases, arising in the ureter. Both patients were young adult males. Histology of both cases was similar, showing tubules lined by columnar cells with hobnailing of nuclei. Immunohistochemically, both cases resembled their counterparts in urinary bladder. These lesions are important to recognize, since they can easily be confused with several malignancies.